Mating Activates NMDA Receptors in the Medial Preoptic Area of Male Rats. - Dominguez, Juan M.; Balfour, Margaret E.; Lee, Han S.; Brown, Jennifer L.; Davis, Brooke A.; Coolen, Lique M. (Behavioral Neuroscience, 2007)
Studies have emphasized the role of the medial preoptic area (MPOA) as an important site for the regulation of male sexual behavior. Indeed, ablations of the MPOA impair sexual behavior, whereas stimulation of the MPOA enhances behavior. Furthermore, neural activity in the MPOA increases with mating. The current study tested the hypothesis that activation of N-methyl-D-aspartate (NMDA) receptors occurs in MPOA neurons and is essential for the expression of male sexual behavior in rats. Results indicate that nearly all MPOA neurons that expressed Fos following mating also contained the NR1 subunit of NMDA receptors. Furthermore, mating increased phosphorylation, thus activation, of NR1 in the MPOA. Additionally, blocking NMDA receptors significantly decreased mating-induced Fos expression and mating-induced phosphorylation of NMDA receptors and impaired male sexual behavior. These results provide evidence that mating activates NMDA receptors in the MPOA and that this activation is important for the expression of male sexual behavior. Reprinted by permission of the publisher.